Modification of the Corrosion Properties of a Model Fe-8Ni-18Cr Steel Resulting from Plastic Deformation and Evaluated by Impedance Spectroscopy. (9th October 2012) - Girardin, Pierre-Yves; Frigerio, Adrien; Berthod, Patrice
Abstract : A model {minor elements}-free Fe-8Ni-18Cr alloy (wt%) was elaborated by foundry, then cut in several cylindrical parts which were subjected to compression tests leading to different plastic deformation rates. The axis surface of the obtained samples were characterized in corrosion by impedance spectroscopy in an acid sulphuric solution. The obtained EIS results were plotted in the complex plan of Nyquist and the diagrams were all semicircular but with an average radius decreasing when the deformation rate increased. The plastic deformation obviously induced a decrease in charge transfer resistance, revealing a detrimental effect of the corrosion behaviour as the most often reported in studies involving stationary methods of electrochemical characterization of corrosion. It was also found that the capacitance tends to increase with the rate of plastic deformation by compression.